Sistemas de inovação e a mudança econômica nos países de industrialização tardia: uma comparação dos esforços e desempenhos de Brasil e Coreia do Sul - Prizon, Ivan (2017)
This dissertation deals with the economic change of the countries of late industrialization, comparing the Brazilian case to the South Korean in two periods of time. The first period is from the 1950s to the 1980s, in which both countries were technologically catching-up with the more developed countries, and a second period goes from the 1980s until the 2010 decade, when Brazil falling-behind technological, and South Korea teamed up with the developed countries and start to lead the technological development process. For this, a neoschumpeterian and structuralist theoretical framework was used and as well the concepts of Innovation Systems and Economic Change as nuclear concepts. The economic complexity tools, Product Space and the Economic Complexity Index (ECI) was used to observe the economic trajectories. In this approach trade variables are used as a proxy to understand the different economic and technological performances of the countries. The Economic Complexity Index (ECI) shows that South Korea since the beginning of the period of analysis gradually joins with the developed countries, appearing in the second period of analysis among the countries with the most complex economies in the world. The ECI reveal, corroborating with the theoretical framework adopted, that during the period of technological catching-up (1955-1980), Brazil gradually gained better positions, however, from the 1980s forward it successively lost positions in the economic complexity ranking. While the Product Space illustrates the structural change in the economies of 1962 to 1981, when the structural change in the Brazilian and South Korean economy was significant, diversifying and sophisticating the export agenda, from 1981 to 2014 in the South Korean economy, structural change continues to occur substantially increasing production sophistication, but the Brazilian economic structure does not observe any relevant changes, the diversification remained similar to 1981 and without the sophistication of production. It was verified that the structural changes promoted by both countries led to the trajectory of technological catching-up, however, while South Korea continued to promote structural change by adapting its development model, and moved forward in the technological development, while Brazil abandoning its already exhausted model of import substitution without substitution by another model, resulting in the end of the promotion of structural changes and the trajectory of technological falling-behind. Structural analysis through the approach of economic complexity makes it possible to understand why South Korea has moved on and Brazil has lagged behind.